(untitled) (University of Khartoum Engineering Journal, 2022)
GEOMETRIC, aesthetic, and economic considerations have led to the increased use of horizontally curved girders for highway bridges and interchange facilities which involve curved alignment. The current paper investigates the behavior of steelconcrete curved composite bridges. An experimental program was conducted to investigate the behavior of steel-concrete composite curved and straight bridges, through the comparison of the deflection and longitudinal slippage at failure state of the specimens under static load. Three different specimens were built, two were horizontally curved; one of the curved specimens with full interaction, while the other with partial interaction between the concrete and the steel girders, and the third one was straight. Each specimen has three I-girders acted parallel connected with X shape cross frames. All specimens dimension scaled as 1/10 in both length and radius of curvature, of Federal Highway Administration (FHWA) full scale model. The Models were examined in the structure laboratory of American University in Cairo (A.U.C.). The static load was applied incrementally and distributed at six points till failure. Linear Variable Differential Transducer, (LVDT) were used to measure the deflection at girders centers and the longitudinal slip. The results show that the configuration of curved geometric specimens clearly affects the pattern of yield and resistance capacity of the specimens. The maximum deflection of the straight model was in the middle girder while it was at the external girder in the curved specimens. The strength of the partial interaction specimen was 15.83% less than the full interaction model, while the straight model showed the maximum capacity of resistance.